Efficacy, safety, and pharmacokinetics of subcutaneous azacitidine in Taiwanese patients with higher‐risk myelodysplastic syndromes. Issue 5 (25th January 2017) - Chou, Wen‐Chien; Yeh, Su‐Peng; Hsiao, Liang‐Tsai; Lin, Sheng‐Fung; Chen, Yeu‐Chin; Chen, Tsai‐Yun; Laille, Eric; Galettis, Anoula; Dong, Qian; Songer, Steve; Beach, CL
Abstract: Aim: Clinical and pharmacokinetic effects of azacitidine in higher‐risk myelodysplastic syndromes were established in mainly Caucasian populations. Because of inter‐ethnic genotype variability of drug‐metabolizing enzymes, it is important to evaluate azacitidine in populations expected to use the drug. Methods: In this single‐arm study, Taiwanese patients with higher‐risk myelodysplastic syndromes received azacitidine 75 mg/m 2 /day for 7 days/28‐day cycle for up to six cycles. Response‐evaluable patients had baseline and cycle 6 marrow assessments. Clinical outcomes are compared descriptively with those from a phase 3 study comprising mainly Caucasian patients ( N = 179). Pharmacokinetics in a subgroup of Taiwanese patients are descriptively compared with a historical control of North American patients ( N = 45). Results: Median age of Taiwanese patients ( N = 44) was 64 years (range 36–90), and 46% had poor cytogenetics. Median number of azacitidine cycles was six (1–6). No response‐evaluable patient ( n = 33) achieved complete or partial remission; however, 22 patients (50%) achieved hematologic improvement, 12 of 32 patients attained RBC transfusion independence and 7 of 18 attained platelet transfusion independence. Most common grade 3–4 treatment‐emergent adverse events were neutropenia (52%) and leukopenia (39%). Pharmacokinetic profiles were similar for Taiwanese ( N = 12) and North American ( N = 45) patients. Maximum plasma concentration was higher in Taiwanese patients; however, mean azacitidine exposure was within the range for North American patients. Conclusion: These data confirm the safety and efficacy of azacitidine in Taiwanese patients with higher‐risk myelodysplastic syndromes. Clinical outcomes were generally comparable with those for Caucasian patients. No meaningful differences in azacitidine pharmacokinetics were observed for Taiwanese patients, and no initial dose adjustment is necessary.